Analisis Digitalisasi Layanan Keuangan dan Kepuasan terhadap Loyalitas Nasabah Bank Syariah Indonesia Kota Bandung (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of digitalization of financial services and customer satisfaction on customer loyalty at Bank Syariah Indonesia (BSI) Bandung City Branch. The background of the research is based on the rapid development of digitalization in the banking sector, especially after the COVID-19 pandemic which has accelerated the adoption of digital financial services. Digital transformation such as mobile banking and internet banking is expected to improve operational efficiency, ease of access, and provide a better transaction experience for customers. This study uses a quantitative method by collecting data through a questionnaire distributed to customers of BSI Bandung City Branch. Data analysis was carried out by validity, reliability, classical assumption test and multiple linear regression test to ensure the accuracy and consistency of the research instrument. The results of the research are expected to provide an understanding of the relationship between the digitization of financial services and customer satisfaction to customer loyalty, Additionally this can serve as a strategic input for bank management in enhancing digital services to retain and boost customer loyalty amid the intensifying competition in the banking industry.